Marriage and Consumption Insurance: What's Love Got to do With It? - Gregory D. Hess (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper explores the role of marriage when markets are incomplete so that individuals cannot diversify their idiosyncratic labor income risk. Ceteris paribus, an individual would prefer to marry a hedge (i.e. a spouse whose income is negatively correlated with her own) as it raises her expected utility. However, the existence of love complicates the picture: while marrying a hedge is important, an individual may not do so if she finds someone with whom she shares a great deal of love. Is love more important to a lasting marriage than economic compatibility? To answer this question, I develop a simple model where rational individuals meet, enjoy the economic and non-pecuniary benefits of marriage (i.e. love), and then must decide whether to remain married or divorce.The model predicts that if love is persistent and the resolution of uncertainty to agents' income is early, then those who in fact married hedges (and for good reason) are the ones most likely to be caught short with too little love in order to save a marriage in the event of an adverse shock. Consequently, under these conditions individuals who are good hedges for one another are more likely to marry one another, although once married, they will be more likely to divorce.In contast, if love is temporary (in the sense of reverting to a common mean) and the resolution of uncertainty to agents' income is predominantly later, then those who in fact marry hedges will in fact be less likely to subsequently divorce. Evidence is provided to distinguish which of these alternative scenarios is in support of these aspects of the decision to stay married. Additional hypotheses regarding the effect of differences in the expected means and volatilities of partners' incomes are also derived from the theory and tested.
Keywords: 330; Consumption Insurance; Marriage